The Role of Work Motivation as a Mediator for the Relationship between Job Satisfaction and Employee Performance at PT Telkom Divre VII Makassar - Ampauleng Ampauleng; Salma Abdullah; Edy Jumady (Universitas Dharma Wacana, 2022)
This study aims to examine and analyze the effect of job satisfaction on work motivation and employee performance and to analyze the effect of work motivation on employee performance at PT. Telkom Divre VII Makassar. This type of research is quantitative and the data source used in this study is secondary data by collecting related data files and using primary data obtained from questionnaires with purposive sampling technique used in determining the sample. The population of the research object is 163 and the number of samples determined is 62 respondents using the Slovin formula. The results of the questionnaires obtained from the respondents have been tested by instruments consisting of validity tests and reliability tests. The data analysis method used is descriptive statistics with the help of the SPSS program. The hypothesis testing used is the sobel test. The results of this study indicate that job satisfaction has a significant positive effect on work motivation, work motivation has a positive effect on employee performance and work motivation has a positive effect on employee performance. Work motivation is not able to mediate significantly between the effect of job satisfaction on the performance of employees of PT. Telkom Divre VII Makassar